Kelayakan Buku Saku Elektronik “Mangifera di Bantaran Sungai Desa Beringin Kencana” sebagai Materi Pengayaan Konsep Keanekaragaman Hayati - Syifa Fauzia; Hardiansyah Hardiansyah; Mahrudin Mahrudin (Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Research and development is oriented towards field data. The results of the field research were then developed into an HTML 5-based electronic pocket book. The electronic pocket book contains Mangifera diversity on the riverbanks of Beringin Kencana Village as material for enriching the concept of biodiversity. The aim of the study was to describe the feasibility of the electronic pocket book